O discurso dos profissionais sobre a demanda e a humanização What do professionals have to say about the demand and humanization of health services - José Roque Junges; Rosangela Barbiani; Raquel Brondisia Panizzi Fernandes; Jessica Prudente; Rafaela Schaefer; Vanessa Kolling (Universidade de São Paulo, 2012)
A humanização dos serviços da atenção primária à saúde depende, em grande parte, da resolução das necessidades em saúde e da conseqüente organização da demanda. OBJETIVO: O artigo objetiva conhecer as implicações da demanda sobre a humanização das práticas de atenção primária. METODOLOGIA: Trata-se de uma pesquisa exploratória com abordagem qualitativa. O universo empírico da pesquisa foi composto por 10 trabalhadores de uma Unidade Básica de Saúde: 1 gestora, 1 médica, 1 dentista, 2 enfermeiros, 3 técnicos em enfermagem, 1 atendente da portaria e 1 encarregado do almoxarifado. A coleta de dados aconteceu em 8 reuniões de discussão focal sobre temas como política de humanização, direito à saúde, integralidade, acolhimento, subjetividade em saúde, processos de trabalho. As discussões foram gravadas e transcritas. Os dados foram trabalhados pela análise do discurso. RESULTADOS: Como resultados, apareceram três repertórios lingüísticos ligados à demanda: compreensão das necessidades em saúde; entendimento do acolhimento como triagem e aplicação de protocolo; influência do modelo biomédico na organização dos serviços. A excessiva demanda e a falta de resolubilidade estão ligadas a uma compreensão das necessidades de saúde como o simples acesso à tecnologia, e do acolhimento apenas como triagem de sintomas. Os profissionais da enfermagem reportam como uma causa da excessiva demanda o fato de que os usuários sempre querem ser atendidos pelo médico, o que pode ser explicado pela cultura da atenção criada pelo modelo biomédico no qual eles próprios se encontram quando entendem as necessidades e o acolhimento na perspectiva biomédica. Humanization of Primary Health Care Services depends mostly on the resolution of the health needs and on the consequen organization of demand. OBJECTIVE: The article searches to know the implications of demand to the humanization of Primary Health Care practices. METHODOLOGY: It is an exploratory research with qualitative approach. The empirical universe was formed by 10 professionals: 1 manager; 1 physician; 1 dentist; 2 nurses, 3 nursing technicians; 1 reception attendant; 1 stockroom commissioner. Data were collected through 8 meetings in which discussion focused on themes such as humanization policy, right to health, integrality, users' reception, subjectivity in health, work processes. The discussions have been recorded and a transcription was made. Analysis of data was done through discourse analysis. RESULTS: As results, three linguistic repertories were found linked with the demand: the understanding of health needs; the understanding of users' reception as screening and application of protocols; the influence of the biomedical model in the organization of the services. The excessive demand and the lack of resolution are linked to the understanding of heath needs simply as access to technology, and of users' reception simply as screening of symptoms. Nurses claim that excessive demand is due to users always wanting to be seen by a physician, which can be explained by the health care culture created by the biomedical model which is also adopted by professionals when they understand health needs and the users' reception in the biomedical perspective.